Intranasal vaccines adjuvanted with Nexavant demonstrate robust protective efficacy by inducing both mucosal and systemic immunity in a murine model - Ko, Kwang Hyun; Bae, Hyun Shik; Lee, So Min; Park, Somin; Han, Seung Hyun; Heo, Jun; Kim, Jinil; Cho, Yerim; Kim, Dong-Ho; Cha, Seung Bin (Frontiers in Immunology, 2026)
Mucosal vaccines offer the advantage of inducing immunity at pathogen entry sites; however, concerns about safety and limited efficacy have hindered the widespread use of viral-vectored intranasal vaccines. Nexavant (NVT), a well-defined TLR3 agonist, was investigated as a non-viral mucosal adjuvant. NVT was formulated with commercial subunit and polysaccharide–protein conjugate antigens and administered intranasally to mice. NVT-adjuvanted vaccines elicited robust mucosal IgA and systemic IgG responses, enhanced antigen-specific CD4+ T cell activation, and conferred strong protection against high-dose influenza virus challenge. Antigen-specific mucosal IgA was detected not only in nasal washes but also in distal mucosal sites such as saliva, vaginal washes, and feces, indicating broad mucosal immune crosstalk. These immune responses were abolished in IFNAR1-/- mice, demonstrating a critical role for type I interferon signaling in NVT’s mechanism of action. The adjuvant was effective across diverse antigen types and demonstrated a favorable safety profile. These findings support NVT as a promising mucosal adjuvant platform for next-generation intranasal vaccines.